Analiza uczniowskich błędów – narzędzie polityki edukacyjnej kraju? - Mirosław Dąbrowski (Problemy Wczesnej Edukacji)
Error analysis has been in use as a tool of improving the mathematics teaching – learning process since the 30s of the last century. In Poland, however, this method of developing mathematics teachers’ skills has been shown some interest since not earlier than 30 years ago. Moreover, it doesn’t seem to be in common use nowadays. Meanwhile, with the growing popularity of external exams and all kinds and levels of skills examining, error analysis may not only help with developing an individual teacher’s professional skill, but can also become a tool for improving the quality of the mathematics educational system in global terms. It seems to be essential because the most important tools used in our educational policy – core curriculum and external exams – are likely to reinforce some categories of pupils’ errors and so become misleading in the difficult process of school mathematical education. The above will be illustrated with some examples taken from pupils’ mathematics skills examining carried out within the last few years.